Medición Del Impacto Con La Implementación Del Software Contable- Administrativo FUDO Dentro De La Compañía Yami Food (2022)
The present investigation is to design a proposal for IMPACT MEASUREMENT WITH THE IMPLEMENTATION OF THE ACCOUNTING- ADMINISTRATIVE SOFTWARE FUDO WITHIN THE YAMI COMPANY. Its main axis is the system accounting, but, along with this, improvements will be made to other areas such as the logistics and of inventories, which are pillars in the generation of management strategies. He The project has been developed as follows: an analysis of research was carried out similar and then some antecedents are determined that help the formulation of the problem. It also shows a state of the art that describes research sources of Other authors. This project is carried out in several facets, the first is to search for why it is not performs an adequate internal control in inventories, accounts receivable, accounts payable and cash registers; After that analysis, the second thing is to find a way to have the proposal Complete with which, it will be shown how it is implemented, the importance and the training that would be done to make it functional for the entity, and thus avoid possible fraud or bankruptcy future by measuring the FUDO program in the Yami Food company.